Perceived Risk and Associated Factors towards COVID-19 infection among the residents of Ondo State, Southwest Nigeria - Elvis Efe Isere; Ikeoluwapo Ajayi; Adewale Moses Adejugbagbe; Samuel Femi Abiona; Nosa Eniye Omorogbe; Omotola Tolulope Akinrinade; Faizah Tosin Okunade; Tolulope Folarin (University of New South Wales, 2022)
'Background' Perceived risk is an important factor in understanding why and how a population adopts health-prevention interventions. When diseases are perceived as low-risk, motivation to use and adhere to prevention interventions is low, which can aid the spread of highly infectious diseases such as COVID-19. In this study, we assessed risk perception and its associated factors towards COVID-19 infection among the residents of Ondo State, southwest Nigeria.   'Methods' A community-based, cross-sectional study design using a multi-stage sampling technique was used to recruit 593 heads of households in three local government areas (LGA) in Ondo State. Data were collected using an interviewer-administered questionnaire which captured information on sociodemographic variables, knowledge of COVID-19 prevention, COVID-19 infection prevention and control practices, and risk perception from September 1 to 30, 2021.   'Results' The respondents were mostly males 357 (60.2%). The mean age of respondents was 37.5±14.7 years with 409 (69%) between the age group of 20 to 40 years. Slightly more than one quarter of respondents were civil servants and 78.4% were of Yoruba ethnicity. More than three quarters, 522 (88%), of the respondents had good knowledge of COVID-19 and its preventive measures. The mean risk perception score was 49.0±12.1. Respondents who were civil servants, had good knowledge of COVID-19 and its preventive measures, had lower household income, and were of Yoruba ethnicity had significantly higher risk perception towards COVID-19 infection compared to other groups. Higher risk perception was associated with preventive measures, such as handwashing.   'Conclusion' Our study shows a high-risk perception towards COVID-19 infection among residents in Ondo state, Nigeria. However, there were significant differences between varying knowledge levels, ethnic groups and civil versus non-civil servants. In view of this, we recommend intensified risk communication interventions targeting these groups to improve their risk perception to change health-protective behaviour towards COVID-19 infection.''